EVALUASI KEPATUHAN PENGGUNAAN APD PETUGAS CLEANING SERVICE DALAM MENDUKUNG PROGRAM PPI DI RUMAH SAKIT X - Awalia Azra Sahara (Rena Cipta Mandiri, 2026)
Hospitals are healthcare facilities with a high risk of infection transmission to patients, healthcare workers, and supporting staff. One of the important efforts to prevent infection is the implementation of the Infection Prevention and Control (IPC) program, including compliance with the use of Personal Protective Equipment (PPE). This study aimed to evaluate PPE compliance among cleaning service staff in supporting the IPC program at Hospital X. This study used a descriptive quantitative design. Data were collected through direct observation and PPE compliance monitoring records from the IPC unit. Problem analysis was conducted using the USG method (Urgency, Seriousness, Growth), while root causes were analyzed using a Fishbone diagram. The results showed that PPE compliance from October to December was above 90%, namely 91.0% in October, 92.9% in November, and 91.6% in December, but had not reached the optimal standard of 100%. USG analysis identified PPE non-compliance as the main problem. Fishbone analysis indicated that the issue was influenced by individual, method, management, and environmental factors. Improvement efforts were carried out using a Lean Management approach by installing PPE reminder posters to increase staff awareness and compliance.